1998
DOI: 10.1161/01.res.82.7.819
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Pulmonary Nitric Oxide in the Acute Phase of Endotoxemia in Rats

Abstract: We present for the first time direct continuous assay of NO concentration (porphyrinic sensor) in the lung parenchyma of Sprague-Dawley rats in vivo during endotoxemia. Intravenous infusion of lipopolysaccharide (LPS, 2 mg x kg(-1) x min(-1) for 10 minutes) stimulated an acute burst of NO from constitutive NO synthase (NOS) that peaked 10 to 15 minutes after the start of LPS infusion, mirroring a coincident peak drop in arterial pressure. NO concentration declined over the next hour to twice above pre-LPS infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…26 The literature concerning the role of NO in endotoxic shock is, however, confusing with reports of both protective and deleterious effects, for example, although infusion of L-nitromonomethyl arginine may transiently improve blood pressure, there may be a marked reduction of survival. 27 Several studies have shown that both Kupffer cells and hepatocytes themselves synthesize NO. 28,29 In LPS treated rats portal and systemic plasma nitrite and nitrate levels (considered markers of NO production) are increased over 40-fold compared with normal rats as a result of iNOS induction by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…26 The literature concerning the role of NO in endotoxic shock is, however, confusing with reports of both protective and deleterious effects, for example, although infusion of L-nitromonomethyl arginine may transiently improve blood pressure, there may be a marked reduction of survival. 27 Several studies have shown that both Kupffer cells and hepatocytes themselves synthesize NO. 28,29 In LPS treated rats portal and systemic plasma nitrite and nitrate levels (considered markers of NO production) are increased over 40-fold compared with normal rats as a result of iNOS induction by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that NO production occurs by a mechanism independent of PAF might be teleologically advantageous. Others report that prevention of NO synthesis greatly worsens cellular and organ dysfunction attributed to PAF during endotoxemia or bacteremia [33][34][35]. Especially in the lung, NO may exert a protective effect [34].…”
Section: Discussionmentioning
confidence: 99%
“…iNOS is thought to play a pivotal role in endotoxemia, and NO concentration has been measured in endotoxemia by insertion of an NO-sensitive porphyrin microelectrode in the lung [110], in the aorta wall [111], or in the pulmonary artery wall [112]. Injection of lipopolysaccharide to induce endotoxemia was followed by a decrease in systemic arterial pressure, and a transient increase in NO (baseline 50 n M , peak 150 n M NO) which lasted 20 min was measured both in the aortic wall [110] and lung tissue [111].…”
Section: Applicationsmentioning
confidence: 99%
“…Injection of lipopolysaccharide to induce endotoxemia was followed by a decrease in systemic arterial pressure, and a transient increase in NO (baseline 50 n M , peak 150 n M NO) which lasted 20 min was measured both in the aortic wall [110] and lung tissue [111]. A second slower rise was recorded in the pulmonary artery at 45 min [112].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation